Sistem informasi steam kendaraan berbasis web menggunakan framework laravel di steam nyomplong - didit supriyadi; Adhitia Erfina (Computer Science and Information Technology, 2023)
Along with the times, the application of technology has spread to various fields, one of which is the service sector. Many companies are competing to get customers by utilizing technology, one of which is with a web-based application. In the field of steam washing services, these nyumplong vehicles are still unable to take advantage of technological developments. This is a problem for the nyomplong steam wash, where in the service process it is less effective in cashier payments, still uses manual transaction methods, and income reports still use notes on the book. The purpose of this research is to make a vehicle washing service application on steam nyomplong uses PHP and MySQL which can facilitate payment transaction activities at cashiers and the steam nyomplong data collection process. Includes the stages of system analysis, design, interface design and implementation, and testing. Based on the research that has been carried out, it produces an application that can make it easier for the steam nyomplong to manage data collection and transaction processes at the cashier, practical to use at the steam nyomplong.